The value of clinical trial medication and yearly medicine cost avoidance from clinical trials conducted by the pharmaceutical industry in Finland - Bengtström, Mia Marina; Tamminen, Nadia; Laaksonen, Niina; Pakkala, Seppo; Juppo, Anne (International Journal of Clinical Trials, 2023)
Background: Clinical trials have been reported to cause medication cost avoidance (MCA) for hospitals and societies, but there are no studies documenting MCA from the Nordic countries or from the pharmaceutical industry perspective. Methods: Three different methods were tested for determining the yearly MCA in clinical trials conducted by the pharmaceutical industry in Finland. MCA was evaluated with questionnaires to pharmaceutical companies operating in Finland in 2001, 2009 and 2013. Results: In method 1 (year 2001), the MCA in Finland was 70.3 million euros in wholesale price and 50.9 million euros when excluding patients receiving placebo treatment. In method 2 (2009), the MCA was 52.0 million euros in wholesale price and 71.0 million euros in out-sale price i.e. including pharmacy fee and tax. The MCA in method 3 (2013) was 47.2 million euros in wholesale price. The collection of data and the MCA calculation was simple in method 1 (response rate 100%). The methods 2 and 3 were more precise but more time-consuming for the respondents, somewhat affecting the response rate (response rates 90% and 72%, respectively). Conclusions: All three methods covered the majority of industry-sponsored clinical medicine trials (64-100%) representing 59-63 % of all clinical trials conducted in Finland in those years. Regardless of the methods, the study medications provided by the pharmaceutical industry promoted significant cost saving for the society. We recommend method 1 for a general and less time consuming MCA calculation and method 3 for a more precise calculation, to be conducted in survey format and interview.